Heat Shock Protein 70 Protects the Heart from Ischemia/Reperfusion Injury through Inhibition of p38 MAPK Signaling. (21st March 2020) - Song, Nan; Ma, Jiao; Meng, Xiao-wen; Liu, Hong; Wang, Hui; Song, Shao-yong; Chen, Qing-cai; Liu, Hua-yue; Zhang, Juan; Peng, Ke; Ji, Fu-hai
Abstract : Background . Heat shock protein 70 (Hsp70) has been shown to exert cardioprotection. Intracellular calcium ([Ca 2+ ]i ) overload induced by p38 mitogen-activated protein kinase (p38 MAPK) activation contributes to cardiac ischemia/reperfusion (I/R) injury. However, whether Hsp70 interacts with p38 MAPK signaling is unclear. Therefore, this study investigated the regulation of p38 MAPK by Hsp70 in I/R-induced cardiac injury. Methods . Neonatal rat cardiomyocytes were subjected to oxygen-glucose deprivation for 6 h followed by 2 h reoxygenation (OGD/R), and rats underwent left anterior artery ligation for 30 min followed by 30 min of reperfusion. The p38 MAPK inhibitor (SB203580), Hsp70 inhibitor (Quercetin), and Hsp70 short hairpin RNA (shRNA) were used prior to OGD/R or I/R. Cell viability, lactate dehydrogenase (LDH) release, serum cardiac troponin I (cTnI), [Ca 2+ ]i levels, cell apoptosis, myocardial infarct size, mRNA level of IL-1 β and IL-6, and protein expression of Hsp70, phosphorylated p38 MAPK (p-p38 MAPK), sarcoplasmic/endoplasmic reticulum Ca 2+ -ATPase2 (SERCA2), phosphorylated signal transducer and activator of transcription3 (p-STAT3), and cleaved caspase3 were assessed. Results . Pretreatment with a p38 MAPK inhibitor, SB203580, significantly attenuated OGD/R-induced cell injury or I/R-induced myocardial injury, as evidenced by improved cell viability and lower LDH release, resulted in lower serum cTnI and myocardial infarct size, alleviation of [Ca 2+ ]i overload and cell apoptosis, inhibition of IL-1 β and IL-6, and modulation of protein expressions of p-p38 MAPK, SERCA2, p-STAT3, and cleaved-caspase3. Knockdown of Hsp70 by shRNA exacerbated OGD/R-induced cell injury, which was effectively abolished by SB203580. Moreover, inhibition of Hsp70 by quercetin enhanced I/R-induced myocardial injury, while SB203580 pretreatment reversed the harmful effects caused by quercetin. Conclusions . Inhibition of Hsp70 aggravates [Ca 2+ ]i overload, inflammation, and apoptosis through regulating p38 MAPK signaling during cardiac I/R injury, which may help provide novel insight into cardioprotective strategies.